Potential safety issues with blood flow restriction training - Loenneke, J. P.; Wilson, J. M.; Wilson, G. J.; Pujol, T. J.; Bemben, M. G. (Scandinavian Journal of Medicine & Science in Sports, 2011)
The focal point of previous literature was establishing the efficacy of blood flow restriction training with respect to muscular strength, muscular hypertrophy, and muscular endurance. After mounting evidence supporting the efficacy of low-intensity blood flow restriction training, research has shifted to the overall safety of this training modality. The aim of this review was to summarize the research on the overall safety of blood flow restriction training, focusing on the cardiovascular system (central and peripheral), muscle damage, oxidative stress, and nerve conduction velocity responses compared with those observed with regular exercise. Although still sparse, the blood flow restriction training research thus far is promising with respect to safety outcomes. Individuals respond similarly to blood flow restriction training and to regular exercise; however, longer term studies are required to better understand the chronic effects of low-intensity blood flow restriction training and possible safety issues.